Understanding the Use of O and Ga Particles in Japanese Sentences for Japanese Language Learners - Rahma Fitri Alifah; Puspa Mirani Kadir; Yuyu Yohana Risagarniwa (IZUMI, 2020)
Joshi or particle is a class of words that cannot change the form, other than that Joshi cannot stand itself. Joshi must be attached to another class of words to gain meaning. In the Japanese language, one of the joshi groups that can connect noun and noun or noun and verb or adjective called the kakujoshi category, two of them are o and ga particles. One of the functions of o and ga particles have the same function as an object marker; many Japanese language learners still have difficulty in using o and ga particles as an objective marker. This research is how Japanese language learners' understanding of using o and ga particles in Japanese sentences. The method used the quantitative and questionnaire technique. This research concludes that many respondents have passed the advanced level in the Japanese language proficiency test, and need more than two years for study. However, the understanding of Japanese learners in the use of o and ga particles are still at the intermediate level.